Fear of COVID-19 Among College Students: A Systematic Review and Meta-Analysis - Wang, Fang; Zhang, Le; Ding, Lu; Wang, Lei; Deng, Yang (Frontiers in Public Health, 2022)
Background: Mental health issue among college students is routinely a major public health concern and coronavirus disease 2019 (COVID-19) pandemic may have exacerbated the students’ mental health issue. However, previous studies related to the fear of COVID-19 among college students reported a wide range of estimate, which is difficult for the policymakers to propose interventions to cope with the fear. Therefore, we aimed to conduct a systematic review and meta-analysis that quantitatively synthesized the fear among college students during the COVID-19 pandemic. Methods: Pubmed, Embase, CINAHL, and PsycINFO electronic databases were systematically searched to identify cross-sectional study reporting the state of COVID-19 fear examined by the Fear of COVID-19 Scale (FCV-19S) published up until Nov 20, 2021. Methodological quality was complied with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The random-effects model was employed to estimate the pooled mean of FCV-19S score. Subgroup analysis, and meta-regression analysis were also conducted. Publication bias was assessed by Begg’s test and funnel plot. Results: A total of 16 studies with a sample size of 11,872 were included. A pooled mean of FCV-19S score was 17.60 [95% confidence interval (CI): 16.41-18.78]. The mean of COVID-19 fear in women (17.11, 95% CI: 16.59-17.64) was higher than that in men (15.21, 95% CI: 14.33-16.08). The highest and lowest pooled means of FCV-19S score were observed in the studies conducted in multiple countries including Israel, Russian, and Belarus (21.55, 95% CI: 20.77-22.33) and in Europe (16.52, 95% CI: 15.26-17.77), respectively. In addition, the highest and lowest pooled means of FCV-19S score were related to item 1 (3.56, 95% CI: 2.82-4.30) and item 3 (1.78, 95% CI: 1.51-2.05), respectively. No significant publication bias was detected by Begg’s test. Conclusions: College students experienced the fear caused by COVID-19 pandemic. It is necessary to design and implement prevention programmes that target the mental health of college students.